Work and Home Neighborhood Design and Physical Activity. Issue 8 (November 2018) - Carlson, Jordan A.; Frank, Lawrence D.; Ulmer, Jared; Conway, Terry L.; Saelens, Brian E.; Cain, Kelli L.; Sallis, James F.
Purpose: To investigate relations of perceived worksite neighborhood environments to total physical activity and active transportation, over and above home neighborhood built environments. Design: Observational epidemiologic study. Setting: Baltimore, Maryland-Washington, DC, and Seattle-King County, Washington metropolitan areas. Participants: One thousand eighty-five adults (mean age = 45.0 [10.2]; 46% women) recruited from 32 neighborhoods stratified by high/low neighborhood income and walkability. Measures: The Neighborhood Environment Walkability Survey assessed perceptions of worksite and home neighborhood environments. Accelerometers assessed total moderate-to-vigorous physical activity (MVPA). The International Physical Activity Questionnaire assessed total active transportation and active transportation to and around work. Analysis: Mixed-effects regression tested relations of home and worksite neighborhood environments to each physical activity outcome, adjusted for demographics. Results: Home and worksite mixed land use and street connectivity had the most consistent positive associations with physical activity outcomes. Worksite traffic and pedestrian safety were also associated with multiple physical activity outcomes. The worksite neighborhood explained additional variance in physical activity outcomes than explained by the home neighborhood. Worksite and home neighborhood environments interacted in explaining active transportation to work, with the greatest impacts occurring when both neighborhoods were activity supportive. Conclusion: Both worksite and home neighborhood environments were independently related to total MVPA and active transportation. Community design policies should target improving the physical activity supportiveness of worksite neighborhood environments and integrating commercial and residential development.